Poetry and Theology: Evangelical Review of Theology - Martin, D. S. (Evangelical review of theology, 2024)
The article focuses on the intersection of poetry and theology, emphasizing the significance of poetry in conveying spiritual truths and exploring the connections between contemporary poems and their literary predecessors. Topics include the use of poetry to engage with the affective and relational aspects of human experience, the author's inspiration from 17th-century metaphysical poets, and the value of understanding poetry as a spiritual discipline for Christians.